Analisis Pengaruh Kelengkapan Produk, Harga dan Lokasi Terhadap Keputusan Konsumen Berbelanja di Toko New Agung Alat Tulis dan Kantor di Makassar - Kapriani Kapriani; Kurniaty Kurniaty (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
The purpose of this study is to determine the significance of the effect of product completeness, price, and location of consumer decisions to shop at the New Agung Stationery Store and Office in Makassar, either partially or simultaneously. Data collection was carried out by interview and questionnaire, the data collected were primary and secondary data. This study uses the incidental sampling method with a sample size of 98 respondents. The results showed that based on multiple linear regression analysis showed that the variable product completeness (X1), price (X2) and location (X3) had a positive influence on customer decisions. Based on the calculation of the correlation coefficient test (R), the R value of 0.613 indicates a strong relationship. The coefficient of determination (R2) for the customer's decision to save funds is explained by the price of the product and location of 37.6%. Based on the results of the t test shows that the variable product completeness (X1), price (X2), and location (X3) have a significant effect on consumer decisions to shop at New Agung Stationery Store and Office in Makassar. The most dominant factor influencing consumer purchasing decisions is product completeness. The F test shows that the variable product completeness, price, and location simultaneously has a significant effect on consumer decisions to shop at the New Agung Stationery Store and Office in Makassar. Thus the hypothesis proposed in this study is accepted.